(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
The aim of this article is to analyze the aquarium as a spatial figure of social imaginary in three novels written by Chilean authors in the past two decades, Gonzalo Contreras’s El nadador (1995), Alejandro Zambra’s La vida privada de los árboles (2007) and Roberto Bolaño’s Monsieur Pain (1999). My purpose is to inquire about the imaginary configuration of spaces that refer to intimacy and the shelterless in the context of chilean postdictatorship and, more generally, in the global environment of the third stage of multinational capitalism.